Thermal residual stresses in thick film structures resistor on dielectric – FEM analysis - Jakubowska, Małgorzata; Golański, Dariusz; Kaliński, Dariusz; Hotra, Zenon (Видавництво Національного університету "Львівська політехніка", 2002)
This paper presents the results of calculations performed using the finite element method (FEM) which include a comparative analysis of residual stress state induced in thick film structures resistors on dielectrics which differ from one another in materials used to perform dielectric layers. This analysis permitted us to test the materials examined in terms of the level and distribution of the residual stresses developed in the structure.